PhasIR: An Instrumentation and Analysis Software for High-throughput Phase Transition Temperature Measurements. Issue 1 (27th December 2021) - Rodriguez, Jaime; Politi, Maria; Scheiwiller, Sage; Bonageri, Shrilakshmi; Adler, Stuart; Beck, David; Pozzo, Lilo D.
We have designed an open-source and high-throughput thermal analysis system for fast and accurate estimation of phase transition temperatures for up to 96 samples analyzed simultaneously. The results are comparable to current state of the art systems such as differential scanning calorimetry (DSC), which is costly and time-consuming. The PhasIR hardware system utilizes an infrared camera to optically record thermal processes that result from the melting/freezing and/or evaporation of samples, while the accompanying open-source software package allows for subsequent batch analysis and processing to extract phase transition temperatures. The PhasIR system showed good agreement with DSC results for both pure substances and mixtures, such as deep eutectic solvents (DES). The all-in-one hardware and software system can be easily replicated and built using relatively inexpensive components at a total estimated cost of $1, 080 USD. Implementation of the PhasIR system will allow for increased throughput in material thermal characterization and broader investigation of material design spaces. Metadata Overview: Main design files: https://github.com/pozzo-research-group/phasIR Target group: Scientists requiring high-throughput thermal analysis of organic samples (e.g. pharmaceuticals, polymers, food ingredients, greases, solvents). Skills required: CNC machining, 3D printing, basic electronics and programming. Replication: No builds known to the authors so far.